Development of tool life prediction model for PCBN inserts during the high speed end milling of AISI H13 hardened tool steel - Hafiz, A.M. Khalid; Amin, A. K. M. Nurul; Karim, A.N. Mustafizul; Lajis, Mohd Amri (2007)
This paper presents the result of an experimental investigation on tool wear of PCBN tool insert during the high speed end milling of AISI H13 tool steel under dry cutting condition. Sufficient numbers of experiment were run based on the central composite design (CCD) concept of response surface methodology (RSM) in order to generate tool life data. An empirical second order quadratic model in terms of cutting speed, feed and axial depth of cut has been developed for the effective prediction of tool life under particular cutting condition. The adequacy of the model has been verified by ANOVA at 95% confidence interval. From the model it is clear that cutting speed possesses the most dominating effect over tool life followed by feed and axial depth of cut. An increasing cutting speed, feed and axial depth of cut will result in decreasing tool life.